SN IMPLEMENTASI MANAJEMEN PEMBELAJARAN DAN KELENGKAPAN PERANGKAT PEMBELAJARAN GURU TERHADAP HASIL BELAJAR PESERTA DIDIK (STUDI KASUS DI SDN KECAMATAN PANDAAN KABUPATEN PASURUAN): Learning Management, Learning Tools and Learning Outcomes - Nuryati, Susi (Journal of Education Management and Learning, 2020)
The success of an educational goal depends on how the teaching and learning process experienced by students. Effective classroom management is an absolute prerequisite for effective teaching and learning. The function of classroom management is to create a conducive classroom atmosphere in order to improve the quality of learning. The purpose of this study was to determine the partial effect of the implementation of learning management on student learning outcomes and to determine the partial effect of the completeness of teacher learning devices on student learning outcomes and to determine the simultaneous effect of learning management implementation and the completeness of teacher learning devices on student learning outcomes students at SDN in Pandaan Subdistrict, Pasuruan Regency. This research is a type of research that basically uses an inductive deductive approach. This approach departs from a theoretical framework, the ideas of experts, and understanding of researchers based on their experience, in this study using the entire population because of their small numbers. So that in this study as many as 40. This method is called the quantitative method because the research data in the form of numbers and analysis using statistics. The conclusions that can be drawn from the results of multiple linear regression analysis are as follows: 1) Learning management has an impact on the completeness of learning tools, this is seen from the t test where the resulting t-test value of 3,650 with a significant level of 0.001. 2) The completeness of the learning kit has an impact on improving student learning outcomes, and these results are supported by the results of multiple linear regression, namely the t test in which the resulting t-count is 2.841 with a significant level of 0.007. 3) Simultaneous test results can be seen from the resulting F count value of 10,041 with a significance value of 0,000 less than 5%. This shows that good learning management and balanced by the completeness of high learning tools, the learning outcomes of students will be better.